Resurrection, Prophethood, and leadership in the al-RisÁlat al-IÝtiqÁdÁt of al-shaykh al-sadÙq and al-Shaykh al-Mufid - FurÙgh RahimpÙr (حکمت اسرا)
al-shaykh al-sadÙq and al-Shaykh al-Mufid, the two early Imami theologians, examining a variety of issues in the sphere of the fundamentals of religious belief (uÒÙl-i DÐn), and with a ShiÝite doctrinal approach, have bequeathed to posterity some of their findings and insights. Constant examination of the thoughts of the predecessors, particularly when the antiquity becomes highly significant and validating, makes purer views available to scholars. Thus it is of great importance. This article attempts to compare and analyze the positions of al-shaykh al-sadÙq and al-Shaykh al-Mufid concerning the three religious principles of resurrection, prophethood and leadership. In the discussion of the resurrection there is a widespread agreement, despite the discussions of prophethood and leadership, in which there are considerable disagreements. This article, focusing on the RisÁlat al-IÝtiqÁdÁt of al-shaykh al-sadÙq and TashÎh al-IÝtiqÁd of al-Shaykh al-MufÐd, and exploring their other works, undertakes to compare and examine the positions of the two in the afore-mentioned doctrines.